Inclusive directions : the role of the chief diversity officer in community college leadership - Pickett, Clyde Wilson, 1977- (Rowman & Littlefield, 2017)
This book provides an in-depth view of the roles and responsibilities of the chief diversity officer, diversity strategic planning, and examines the various roles of diversity leaders at community colleges and will significantly benefit those interested in learning more about diversity and inclusion at community colleges.